THE EFFECTIVENESS OF THE THINK TALK WRITE (TTW) LEARNING MODEL ON STUDENTS’ SCIENTIFIC COMMUNICATION SKILLS ON ECOSYSTEMS - Pranoto, Hendro (Universitas Negeri Medan, 2024)
Learning model plays a crucial role in improving students' communication skills. This research aims to determine the level of effectiveness of the Think Talk Write learning model on students' scientific communication skills on ecosystem material in class X MAS Al-Wardah. This type of research is descriptive research using a one group pretest-posttest design. The data collected in this research is attitude data on scientific communication skills and written scientific communication skills which are constructed based on six indicators of scientific communication skills. Attitude data on scientific communication skills were collected using the observation method and data on students' written scientific communication skills were collected using the test method. The research results showed that students' scientific communication skills attitudes increased with a gain factor of 0.31 in the medium category and also students' scientific communication skills in writing with an average gain of 0.4 in the medium category. Based on these results, it can be concluded that the Think Talk Write learning model is still less effective in improving students' scientific communication skills.